Pseudomonas aeruginosa bacteremia secondary to acute right leg cellulitis - Abdul Wahab, Asrul; Rahman, M. M. (Technische Universität Dortmund, 2013)
Pseudomonas aeruginosa is a gram-negative bacillus that causes wide spectrum clinical infections. However, it is most frequently associated with hospital-acquired infection. In this case a 58-year-old male with underlying hypertension and dyslipidaemia was admitted for acute right leg cellulitis. Pseudomonas aeruginosa was identified from the case, though it was not a usual suspected organism. It might be due to community-acquired infection.
case of community-acquired infection
EXCLI Journal ; Vol. 12, 2013
Keywords: AmpC; Pseudomonas aeruginosa; community-acquired; cellulitis; bacteremia; 610